Is there a nonlinear relationship between public investment and private investment? Evidence from 21 Organization for Economic Cooperation and Development countries - Marcos, S. S.; Vale, S. (International Journal of Finance and Economics, 2024)
This paper studies the relationship between public investment and private investment in a sample of 21 Organization for Economic Cooperation and Development (OECD) countries between 2000 and 2019. Using panel data nonlinear threshold regression models, the empirical results show that there exist threshold levels for the share of public investment in private investment, the real Gross Domestic Product (GDP) growth rate and the real interest rate that affect the relationship between public and private investment. All estimates support a crowding-in effect of public investment on private investment. In terms of policy prescriptions, by increasing public investment, OECD governments can expect positive spillovers to private investment.